CALCULATION OF INDIVIDUAL ISOTOPE EQUILIBRIUM CONSTANTS FOR GEOCHEMICAL REACTIONS - Thorstenson D.C.; Parkhurst D.L. (My University, 2004)
Theory is derived from the work of Urey (Urey H. C. [1947] The thermodynamic properties of isotopic substances. J. Chem. Soc. 562–581) to calculate equilibrium constants commonly used in geochemical equilibrium and reaction-transport models for reactions of individual isotopic species. Urey showed that equilibrium constants of isotope exchange reactions for molecules that contain two or more atoms of the same element in equivalent positions are related to isotope fractionation factors by α = (Kex)1/n, where n is the number of atoms exchanged. This relation is extended to include species containing multiple isotopes, for example ¹³C¹⁶O¹⁸O and ¹H²H¹⁸O. The equilibrium constants of the isotope exchange reactions can be expressed as ratios of individual isotope equilibrium constants for geochemical reactions. Knowledge of the equilibrium constant for the dominant isotopic species can then be used to calculate the individual isotope equilibrium constants.